Chapter Massimo Quaini, territorialista - Magnaghi, Alberto (Territori, 2021)
The essay illustrates Quaini's inputs to the construction and the theoretical/operational development of the territorialist school and, later on, of the Territorialist Society, of which he was one of the major founders and guarantors. In his explication of concepts like place, territory, landscape, place awareness, Quaini anticipates the need for a multidisciplinary territorialist lexicon. Taking from Herodote Italia the focus on the fundamental integration of historical and spatial knowledge, he recommends a confluence of geography into the territorialist multidisciplinary system, exemplifying it in relation to topics like territorial museums, local observatories of landscape, statute of places, foundational description, new relationships between city and countryside.